2004
DOI: 10.1002/jbm.a.30070
|View full text |Cite
|
Sign up to set email alerts
|

Hemocompatibility of nitrogen‐doped, hydrogen‐free diamond‐like carbon prepared by nitrogen plasma immersion ion implantation–deposition

Abstract: Amorphous hydrogenated carbon (a-C:H) has been shown to be a potential material in biomedical devices such as artificial heart valves, bone implants, and so on because of its chemical inertness, low coefficient of friction, high wear resistance, and good biocompatibility. However, the biomedical characteristics such as blood compatibility of doped hydrogen-free diamond-like carbon (DLC) have not been investigated in details. We recently began to investigate the potential use of nitrogen-doped, hydrogen-free DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 28 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…3, the overall peak shape changes by the addition of nitrogen and the I D /I G ratio reaches a maximum of about 1.8 for small nitrogen contents. This increase for smaller nitrogen contents was reported before [6,9,22]. The graphite structure is modified by the incorporation of the nitrogen due to the presence of bonds between C and N [9].…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…3, the overall peak shape changes by the addition of nitrogen and the I D /I G ratio reaches a maximum of about 1.8 for small nitrogen contents. This increase for smaller nitrogen contents was reported before [6,9,22]. The graphite structure is modified by the incorporation of the nitrogen due to the presence of bonds between C and N [9].…”
Section: Resultssupporting
confidence: 54%
“…Furthermore, a decrease of the I D /I G ratio towards higher concentrations of the added element was found for Si addition, as is the case here with N addition. For N-DLC samples prepared with a cathodic arc plasma source this has also been reported [22]. Those facts were interpreted by a possibly higher hydrogen content and a structural change towards a higher sp 3 /sp 2 ratio as well as smaller average size of the sp 2 clusters, respectively.…”
Section: Resultsmentioning
confidence: 76%
“…However, in experiments in vivo, pyrolytic carbon and pyrolytic graphite/silicon-carbide, implanted into rabbit mandibles, induced fibrous capsule formation and infiltration with multinucleated phagocytic cells (Maropis et al, 1977). On the other hand, similarly as the amorphous hydrogenated carbon, pyrolytic carbon (particularly in the form of so-called Low Temperature Isotropic pyrolytic carbon, LTI) has been used as a coating for commercially available blood contacting devices, such as artificial heart valves (Kwok et al, 2004;Jackson et al, 2006), in order to prevent hemocoagulation and thrombus formation on these devices, although its hemocompatibility was not ideal. LTI has been also used in orthopedic applications, namely for construction of joint replacements, because it has been reported to reduce the cartilage wear (Bernasek et al, 2009).…”
Section: Graphitementioning
confidence: 99%
“…Kwok et al analyzed calcium and phosphorous-doped a-C:H fi lms synthesized by PIII, assessing that both P-DLC and Ca-DLC fi lms presented a smaller number of adhered and unactivated platelets in relation to LTIC, whereas, in contrast, a higher number of platelets was found on DLC doped with a combination of Ca and P (Kwok et al , 2005;Kwok et al , 2006). The same authors demonstrated that the amount of nitrogen is critical for the haemocompatibility of N-DLC fi lms (Kwok et al , 2004). Comparing a-C:N with varying nitrogen content, they showed variable adhesion and activation of platelets, depending on the fraction of sp 2 bonding.…”
Section: Modifi Ed Dlc Fi Lmsmentioning
confidence: 88%